Studying the effect of Spraying Marimareen , Alga and Interaction in Growth , Yield and fruit quality of Snake cucumber ( Cucumis melo. Var. flexuosus naud ) - Jabir, Evan A.A.; Sakr, Mahdy A.A.; Amran, Hisham A. (Journal of Kerbala for Agricultural Sciences, 2016)
An experiment was conducted in the Collage of Agriculture Kerbala University in AL- Husainia region during the growing season of 2014-2015 to study the effect of Organic by Marimareen and Alga up Growth , Yield and fruit quality of Snake cucumber (Cucumis melo.V.Var flexuous naud ) , which Included the first four levels of fertilization count fertilizer Alga which 0,1,2,3 ml/L and the second level was four level of organic fertilizer bal marimareen which 0,1,2,3 ml/L .The experiment design used in this experiment was Randomized Complete Block Design (R.C.B.D) with three replicates , means of treatments was compared using L.S.D at probability level of 0.05 and results to show :- 1-The fertilization organic fertilizer by Marimareen M3 a significant effect is evident in the qualities of vegetative growth and holds the plant quality traits as the best rates for the treatment of spraying a concentration 3ml/L reached 3.017 kg , 9.43 tons / h in yield of plant and total yield while given treatment comparison lowest rates reached 1.911 kg , 5.97 tons / h respectively . 2-The fertilization in organic fertilizer Al-Alga E3 a significant effect is evident in the qualities of vegetative growth and holds the plant quality traits as the best rates were spray for the treatment of concentration 3ml/L reached 3.146 kg , 9.83 tons / h in yield of plant and total yield while given treatment comparison lowest rates reached1.842 kg ,5.76 tons / h respectively . 3-The overlap had a significant effect on vegetative growth and overall quality indicators winning qualities has given the best rates3.635 kg , 11.36 tons / h in yield of plant and total yield when treatment M3E3 compared with the treatment that gave the lowest rates reached 1.418 kg , 4.43 tons / h respectively.